2008
DOI: 10.1177/0960327108092295
|View full text |Cite
|
Sign up to set email alerts
|

Ofloxacin-associated retinopathy in rabbits: role of oxidative stress

Abstract: Ofloxacin, a quinolone, is an extensively used, well-tolerated antibacterial agent but has been reported to induce photosensitivity at low incidences. In the present investigation, the possible role of oxidative stress in ofloxacin-induced retinopathy in rabbits was evaluated. It was observed that ofloxacin at a dose rate of 10 and 20 mg/rabbit, twice daily for 21 consecutive days, resulted in significant elevation in the extent of lipid peroxidation and depletion of the blood glutathione levels. Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
26
2
Order By: Relevance
“…Like other fluoroquinolones, lomefloxacin acts by inhibiting DNA topoisomerases, of which DNA gyrase and topoisomerase IV are particularly important [28,40]. Serious adverse phototoxic reactions on melanin containing tissues (e.g., allergy, toxic dermatitis, retinal degeneration) have been described for the use of lomefloxacin [27,28,36]. This fluoroquinolone belongs to the class of antibiotics known to exhibit severe phototoxicity [37].…”
Section: Introductionmentioning
confidence: 99%
“…Like other fluoroquinolones, lomefloxacin acts by inhibiting DNA topoisomerases, of which DNA gyrase and topoisomerase IV are particularly important [28,40]. Serious adverse phototoxic reactions on melanin containing tissues (e.g., allergy, toxic dermatitis, retinal degeneration) have been described for the use of lomefloxacin [27,28,36]. This fluoroquinolone belongs to the class of antibiotics known to exhibit severe phototoxicity [37].…”
Section: Introductionmentioning
confidence: 99%
“…Among the ocular side effects of this group of antibiotics are: local irritation and burning, hyperemia, eyelid oedema, lid margin crusting, superficial punctate keratitis, corneal precipitation and perforation, blurred vision and lacrimation [2]. Oral administration in animals may result in varied degenerative changes in eye balls, predominantly in retina, due to the increase in lipid peroxidation and generation of free radicals [12]. There are also examples of eye chromosomal DNA fragmentation in Balb/c mice as a result of FQ administration combined with light exposure and reports about the risk of decent in the eye lenses transparency due to the photopolymerization of a-crystallin and damage to the lens epithelial cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in the recent years indicated that fluoroquinolones produce reactive oxygen species (ROS) (Ibrahim and Yarsan, 2011;Rawi et al, 2011). Side effects of these drugs such as phototoxicity and cartilage damage may be related to producing ROS (Pouzaud et al, 2006;Rampal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%